Flow Cytometry Basics for the Non-Expert - Goetz, Christine (Techniques in Life Science and Biomedicine for the Non-Expert,, 2018)
Flow cytometry allows for the measurement of different aspects of a cell or particles in real time. Applications include quantifying various types of T cells to determine the presence of various immune disorders, such as whether HIV has progressed to AIDS, studying the dynamics of immune signaling in cells to detect the suppression of normal immune function, and analyzing biopsy specimens for tumors, to aid in cancer diagnosis and prognosis. In addition to simplifying the technique and using vocabulary accessible to those not trained in cell biology and immunology, the book includes the following 4 unqiue features: 1) Tips on how to set up an experiment for flow cytometry optimially 2) An expanded data set of flow staining including multiparameter flow cytometry 3) Detailed staining protocols for flow cytometry (ex. protocols optimized for transcription factors, secreted cytokines, phospho-antibodies, and surface antigens) 4) Section devoted to antibody development and conjugation.